Analisis Praktik Good Corporate Governance (GCG) Dalam Meningkatkan Kinerja Karyawan (Studi Pada PT. Bank Syariah Indonesia, Tbk. KCP Indrapura, Sumut) - Hamdani, Imam (Journal of Computer Science and Information System(JCoInS), 2024)
The purpose of this study was to determine the application of Good Corporate Governance (GCG) practices in improving employee performance as well as obstacles and efforts made by PT Bank Syariah Indonesia,Tbk KCP Indrapura. The study used qualitative research methods, data obtained from primary and secondary data sources. The results of the study that all employees have signed a commitment to Good Corporate Governance (GCG) to comply with the provisions of BSI legislation and develop a mindset of human resources. In addition, it is founded on standards of professionalism, fairness, accountability, and openness. The implementation of GCG principles is necessary because BSI believes that it is in accordance with Sharia principles. as a form of the company's commitment to PoJK Circular Letter No.8 / PJK.03/2014 and OJK No.10 / SEOJK.03/2014, which regulates the assessment of the soundness of Sharia commercial banks and Sharia business units. The efforts made are the need for supervision from the branch leadership and become a role model for discipline and discipline of officials and employees, discipline in order to achieve good performance goals in order to operate in accordance with applying the principles of Good Corporate Governance (GCG).